Carta de Roberto H. Todd a Antonio R. Barceló - Todd, Roberto H.; Barceló, Antonio R. (My University, 1931)
Reunión con el Lcdo. Feliú
Keywords: Barceló, Antonio R., 1868-1938; Municipal government--Puerto Rico.; Gobierno Municipal--Puerto Rico.